Customer Retention in Service Industry - Siew, Wei Teng; Abu Seman, Noor Aslinda; Harun, Amran (Penerbit UTHM, 2020)
Customer retention is previously considered as the last resort of a company in traditional marketing approach rather than a way to improve long term profit (Krishnan & Govindarajan, 2013). This is because traditional way of marketing strategy tends to focus more on attracting new customers than satisfying the existing customers. However, as globalization continue to precede, low growth and highly competitive marketplace shows that retaining customers is the more effective way to sustain a company against inroad competition. It is found by some studies showing that companies which emphasize on attracting new customers are actually earning to cover up the regular loss of existing customers without them noticing. Thus, winning new customers are considered a risky way to be profitable (Rosenberg & Czepiel, 1984). Many previous literature reviews also showed the importance of customer retention in increasing company revenue. More companies are now changing their marketing and management strategies to reach out to their existing customers in order to prevent them for opting for service provided by competitive company. A number of researches posit that customer retention increase profitability by lowering the cost used to attract new customers. It is supported by studies showing that there is increase in profit to as high as 95% if customer retention of the company increases by 5% (Sharmeela-Banu et al., 2012). Many researchers came into agreement that repeated customers are the more valuable asset compared to new customers in today’s market (Climis, 2016). Meanwhile, it can be seen in today’s world economy, service industry has emerged to be one of the fastest growing sectors among the others. Customers are considered the real asset to service industry due to the nature of this industry which prioritizes relationship between customers with the service (Alshurideh, 2016). This makes it even more crucial for this industry to practice customer retention strategies in order to survive and grow in the very competitive marketplace. As such, this study intends to explore literatures pertaining to definitions, measures, importance and factors that influence customer retention in service industry as well as to discuss on possible strategies to be applied based on the studies.